A Study on Role of NEO Banks in Reducing Financial Stress and Improving Mental Well-being (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Neo banks, also known as digital-only banks or challenger banks, are financial institutions that operate entirely online without traditional physical branches. The concept emerged in response to technological advancements, changing customer expectations, and the need for more efficient, user-friendly, and cost-effective banking services. In countries like India, the neo banking sector is expanding rapidly due to the increasing penetration of the internet and smartphones, supportive government initiatives for digital payments (like UPI), and a large unbanked or underbanked population. Overall, neo banks are transforming the financial services landscape by promoting financial inclusion, enhancing customer convenience, and driving innovation in the banking sector. The study is aimed at analysing the roles, convivence and satisfaction level on Neo- Banking Services. The study is exploratory and is based on primary data collected from 100 samples from Mysuru city of Karnataka. SPSS version 21 was used for data analysis and interpretation. The study found that there is a significance difference in factors with respect to roles, convivence and satisfaction level among respondents. The factors on roles, convivence and satisfaction level have been identified. Therefore, this study would assist students in acquiring the required knowledge to make savings and investment decisions in future in order to reach the desired economic growth.